Peran Pendidikan Agama Islam dalam Membentuk Karakter Toleran dan Inklusif di Era Multikultural - Muhammad Saripuddin B (Khazanah : Journal of Islamic Studies, 2026)
The multicultural context of contemporary society presents both challenges and opportunities for Islamic Religious Education (Pendidikan Agama Islam/PAI) in shaping students’ tolerant and inclusive character. Indonesia’s socio-cultural diversity requires educational institutions not only to transmit religious knowledge but also to cultivate ethical and social values that strengthen social cohesion and harmonious coexistence. This study aims to analyze the role of PAI in fostering tolerant and inclusive character in the multicultural era. The research employs a qualitative approach using a library research design. Data were collected from scholarly books, national and international journal articles, and official policy documents related to religious moderation and multicultural education. The data were analyzed through content analysis, involving data reduction, thematic categorization, and inductive conclusion drawing. The findings reveal that PAI possesses strong normative and pedagogical foundations for character formation through the internalization of universal Islamic values such as compassion (rahmah), justice (‘adl), brotherhood (ukhuwah), and respect for human dignity. The integration of religious moderation principles, multicultural approaches, dialogical learning, contextual case studies, and digital religious literacy emerges as effective strategies for nurturing inclusive attitudes among students. However, the implementation of multicultural-based PAI still faces challenges related to teachers’ pedagogical competence, curriculum design, and institutional culture. Therefore, pedagogical transformation and institutional commitment are essential to ensure that PAI functions as a strategic instrument in developing religious yet humanistic generations capable of living peacefully within diverse societies.